Loss optimization in double fishnet metamaterials at telecommunication wavelengths - Iyer S.; Popov S.; Friberg A. T. (Journal of the European Optical Society-Rapid Publications, 2011)
A hole shape optimization study was made for a double fishnet metamaterial producing a negative index of refraction within 1.4 - 1.5 µm. It is found that within these wavelengths, elliptical holes offer lower losses as compared to rectangular ones and theoretically produce the best figure of merit (FOM) of approximately 6.